2020
DOI: 10.3390/pr8050538
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Steel-Making Dust in Drilling Fluids Formulations

Abstract: Steelmaking is an energy-intensive process that generates considerable amounts of by-products and wastes, which often pose major environmental and economic challenges to the steel-making industry. One of these by-products is steel dust that is produced during the separation of impurities in the smelting and refining of metals in steel-making furnaces. In this study, electric arc furnace (EAF) dust has been evaluated as a potential, low-cost additive to increase the viscosity and weight of drilling muds. Curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The PV increment is related to the increase in solids amount into the drilling mud [80][81][82]. The composition of steelmaking waste, which is similar to bentonite clay, justifies this elevation in rheological parameters [61]. In terms of the 5 Geofluids YP/PV ratio that measures solids' carrying capacity and hole cleaning performance [83], the BASE had a value of 1.64, which was improved to 1.72 by SWM1 and 1.66 by SWM2, but lowered by SWM3 to 1.64.…”
Section: Rheology Measurementsmentioning
confidence: 89%
See 2 more Smart Citations
“…The PV increment is related to the increase in solids amount into the drilling mud [80][81][82]. The composition of steelmaking waste, which is similar to bentonite clay, justifies this elevation in rheological parameters [61]. In terms of the 5 Geofluids YP/PV ratio that measures solids' carrying capacity and hole cleaning performance [83], the BASE had a value of 1.64, which was improved to 1.72 by SWM1 and 1.66 by SWM2, but lowered by SWM3 to 1.64.…”
Section: Rheology Measurementsmentioning
confidence: 89%
“…Massive amounts of waste are produced during the steelmaking process, with waste production projected to reach 2-4 tons per ton of steel generated [59][60][61][62]. The produced wastes were previously used in drill cutting disposal [63,64], asphalt concrete binder [65][66][67], cement production [68][69][70][71], and heavy metal adsorption [72][73][74].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above-mentioned studies have demonstrated the effectiveness of food waste in drilling fluid additives as a substitute for the environmentally hazardous materials currently in use within the industry [ 61 ]. In this regard, there is a need to promote the “waste to wealth” concept by studying the potential of using unused waste derivatives as additives in drilling fluids, and to address the issue by exploring the additives’ rheological properties, which ensure it is viable and cost effective [ 62 ].…”
Section: Waste Derivatives In Drilling Fluidsmentioning
confidence: 99%
“…In the study of Magzoub et al [13], electric arc furnace dust has been evaluated as a potential, low-cost additive to increase the viscosity and weight of drilling muds. Currently, the cost of drilling operations typically accounts for 50% to 80% of the exploration costs and about 30% to 80% of the subsequent field development costs.…”
mentioning
confidence: 99%